Perspectives on the care and advances in the management of children with trisomy 13 and 18. Issue 3 (September 2016) - Carey, John C.; Kosho, Tomoki
Abstract : The trisomy 13 and trisomy 18 syndromes are important and relatively common chromosome conditions each consisting of a recognizable pattern of multiple congenital anomalies, an increased neonatal and infant mortality, and a marked cognitive and motor disability in older children. Because of the medically serious nature of the outcomes, the traditional approach to management in the newborn and early infancy periods has been to withhold technological support and surgery. In the last decade a rich dialogue has emerged in the literature; one view makes the case for pure comfort care for the benefit of the child while the other view supports full intervention in appropriate situations. The principal aim of the series of articles in this issue of the Seminars in Medical Genetics is to enrich and continue this emerging dialogue. The papers include review articles, original research, and commentaries that discuss perspectives on the care and advances in the management of children with the trisomy 13 and 18 syndromes. © 2016 Wiley Periodicals, Inc.